Efficient generation of nitrogen vacancy centers by laser writing close to the diamond surface with a layer of silicon nanoballs. (14th January 2020) - Rong, Youying; Ju, Zhiping; Ma, Qiang; Liu, Shikang; Pan, Chengda; Wu, Botao; Shen, Si; Wu, E
Abstract: We proposed a method to effectively fabricate negatively charged nitrogen vacancy (NV − ) centers close to the diamond surface by applying femtosecond laser writing technique. With a thick layer of silicon (Si) nanoballs coated, diamond surface was irradiated by high-fluence femtosecond laser pulses. A large number of NV − centers were created around the laser ablation crater area without thermal annealing. The distribution of the NV − centers was expanded to about 50 μ m away from the crater center. To demonstrate the function of Si nanoballs, we performed the exactly same laser illumination process on the bare region of the sample surface. In this case, only a few NV − centers were generated around ablation crater. At distance of 32 μ m away from crater centers, the NV − density for the case with nanoballs was up to 15.5 times higher compared to the case without nanoballs. Furthermore, we also investigated the influence of laser fluence and pulse number on the NV − density for the case with Si-nanoball layer. Finally, the formation mechanism of NV − centers and the role of Si nanoballs were explained via Coulomb explosion model. The method is demonstrated to be a promising approach to efficiently and rapidly fabricate NV − centers close to the surface of the diamond, which are significant in quantum sensing. Furthermore, the results provide deep insights into complex light-matter interactions.